LARENKS LİPOMU: BİR OLGU SUNUMU - BİLDİRİCİ, Kısmet; KEÇİK, Cem; PEKER, Betül; İLGİCİ, Dilek (Cerrahpaşa Medical Journal, 2014)
Background.- Laryngeal lipomas are very rare benign laryngeal tumors. They are mostly isolated occurrences and not associated with systemic lipomatosis. To date, there are fewer than 100 cases in the English literature. Observation.- We presented a 51 year-old women patient with extrinsic lipoma that localized in the lingual surface of the epiglottis.